Tuberculosis of the Clivus - Vijay P. Joshi; Shirish Valsangkar; Ashwin Valsangkar; Anish Dekhne; Satish Nivargi; Amit Agrawal (Indian Journal of Neurosurgery, 2017)
The rarity of the tubercular involvement of the clivus makes the preoperative diagnosis difficult. We report a case of a 40-year-old man who presented with right-sided trigeminal neuralgia without any other neurological symptoms or deficits. Postcontrast images showed a dural-based lesion in the region of the clivus which was isointense on T1 images and hypointense on T2 images and the lesion was enhancing after contrast administration suggestive of a tumor. The patient underwent surgical excision of the lesion and the histopathological examination was suggestive of tuberculosis. The patient completed the course of antitubercular therapy and recovered well. Tuberculosis of the clivus region runs an indolent course and following appropriate treatment these patient do well.